Horizontal flow reactor optimization for biogas recovery during high solid organics fermentation: Rheological characteristic analyses. (April 2021) - Wei, Liangliang; Ren, Yimin; Zhu, Fengyi; Xia, Xinhui; Xue, Chonghua; Yang, Haizhou; Ding, An; Zhao, Qingliang
Graphical abstract: Highlights: Rheology index of MOSW declined significantly with an increase in solid contents. Optimized paddle with 0.6D stirring diameter, 0.75D screw pitch and 0.15D eccentricity. Stirring speed of 10 rpm was recommended, observed an energy consumption of 48.2 kJ/m 3 . Viscosity and torque were the key factors in the direct increase in power consumption. Abstract: Continuous improvements in human living standards, water supply quality, and poor solid waste collection systems in China has led to increased production of municipal sewage sludge and organic solid waste (MOSW), which incurs a potential risk for human health and the environment. Solid anaerobic fermentation, which has exhibited advantageous energy recovery and biosolid stabilization, has been considered for urban organic solid waste treatment. The primary objective of this study was to optimize horizontal flow reactor operations for the efficient fermentation of high solid organics and subsequent biogas production via rheological characteristic analyses. The effects of operational parameters, such as paddle type, paddle diameter, pitch diameter ratio, stirring efficiency, torque, and power consumption, on the reactor performance were simulated using computational fluid dynamics (CFD). The solid content greatly influenced the rheological characteristics of the MOSW; increasing the solid content (5 %–30 %) of the MOSW led to a significant decline in the rheological index (0.532 to 0.224). The optimized parameters simulated by CFD included a screw-type stirring paddle with a pitch of 0.6 D, pitch of the screw with the value of 0.75 D, stirring shaft (set vertically and eccentrically downward) with the value of 0.15 D, and stirring speed less than 10 rpm. Moreover, the higher the consistency coefficient, the lower the rheological index and required power consumption. The reactor energy consumption analysis indicated that the average energy consumption can reach 48.20 kJ/m 3 with an efficient operation.